EFFICIENCY OF THE USE OF WORKFORCE AT UKRAINIAN ENTERPRISES IN THE WAR AND POST-WAR PERIODS - DASHKO, Iryna; CHEREP, Oleksandr; MYKHAILICHENKO, Lubomir (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The problems of the use of labor force at the enterprises of Ukraine in the war and post-war periods have been studied. The specifics of the impact of the war on various industries have been determined. The possibility of profitability of the enterprise during the war is analyzed. The business development potential in Ukraine was assessed. A comprehensive assessment was carried out in the study and description of the development processes of the enterprise during the war. A map of entrepreneurship in Ukraine has been developed: needs, interests and opportunities to support a sustainable economy, recovery, peace and business development. The average number of the employed population by types of economic activity for 2018-2022 was analyzed, and the dynamics were made based on the data of the analysis. The dynamics of labor supply and demand in Ukraine for 2018-2022 were carried out. A forecast balance of labor demand was made in comparison with 2022 to 2025. Based on the combination of labor supply and demand, certain conclusions were drawn regarding the potential imbalance of qualifications in the labor market. Proposals for vacant positions and the rate of the unemployed on the labor market by region in Ukraine in 2022 have been developed and substantiated. The number of applicants for 1 vacancy in 2020-2022 has been calculated. A number of statistical indicators for the analysis of the functioning of the Ukrainian labor market are singled out, in particular: the number of labor resources; the number of persons of working age; the number of economically active population; the number of people employed in the economy; the number of part-time workers at the initiative of the administration; the number of job seekers; the number of registered citizens; the number of issued unemployment benefits, etc. The need for the economic growth of the enterprise was determined, the key aspect of which is the motivation and development of labor resources at all its levels. The projected level of unemployment until 2025 has been developed. A recovery program has been developed from the point of view of the economic success of the country, which has a long-term nature and can be developed and refined as the country’s economy develops and interacts with world markets, and is applied to the demilitarized zone, which will allow for the analysis of weak points, check the stability of the system to external factors and work from the point of view of development.